Indigenous Communities: Resisting Ecocentric Sustainability within Rural Tourism - Amparo Miranda Zambrano, Gloria; Vidaurri Aréchiga, José Eduardo (Téoros)

(untitled) (Université du Québec à Montréal, 2014)
Agricultural, communal, and indigenous communities, organized as ejidos, have for centuries shown an ecocentric and devoted relationship with Nature, humanity, and the planet, and continue to apply their values in the development of rural tourism that promotes sustainability. This is an alternative archetype to the Western development paradigm (whose universalist, one-dimensional, and egocentric viewpoint has alarming impacts to the planet and humanity). Our study addresses the expressions of resistance and preservation of natural property and heritage under the guise of rural tourism services within two indigenous communities in Mexico. Our methodology was based on “participative research-action,” where ejidatarios (members of an ejido) and elders reflected on their contribution to rural sustainability. Despite the onslaught of the Western model of global development, in the midst of the 21st century we find the expression of a strong cultural and cosmological identity that expresses a particular form of relationship, both material and spiritual, with Nature—defending and re-creating an environmentally sustainable culture through multiple strategies (encompassing tourism, land, territory, and cultural identity) in the face of the worldwide onslaught and divestment of indigenous peoples. The results of this study provide substantive and symbolic values for similar areas of study.